A kinematic concept for robotic assisted dental rehabilitation / Muhammad Azmi Ayub... [et al.] - Ayub, Muhammad Azmi; Azni, Mohd Shafiq; Al-Jaf, Nagham; Norman, Noraina Hafizan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
The current technique of dental rehabilitation relies largely on the qualitative perception of the dentist in the relocation and reorientation of the teeth. Furthermore, the patient does not have the final visual appearance of the teeth after the procedure. In this project, we plan to address this issue by ultimately developing a concept of robotic assistant dental rehabilitation. The key elements in the concept consist of cone-beam computed tomography machine (CBCT), image processing algorithm and a robot manipulator system, which will function as an integrated unit to aid and guide the dentist in the diagnosis and treatment procedures. The aim of this paper is to show the kinematics concept that relates the dental configuration system with the dental operatory. A homogeneous transformation matrix that relates the key elements of translation and rotation in the robotic work cell concept is developed. From this matrix, the positions and orientations of any tooth can be determined. The relationship between any arbitrary points relative to a tooth frame can also be defined. The formulation of kinematics model for the robotic work cell is discussed. This new model will aid the dentist in the exploration, manipulation and reconfiguration in the dental rehabilitation.